Информационная технология чтения маркировочных надписей компонентов печатных узлов - Antoshchuk, S. G.; Krylov, V. N.; Shcherbakova, G. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
An information technology has been developed that meets the requirements of automated optical inspection systems for reading marking inscriptions of printed assembly components. The technology is based on the application of the hyperbolic wavelet transform, which has improved the reliability of recognizing marking inscriptions.